EFEKTIVITAS PAK OGAH DALAM MENGATUR LALU LINTAS PERSPEKTIF MAQASIDH AL-SYARIAH - Ahmad Zaky Fuad (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
This research aims to understand, identify, and analyze the phenomenon of the prevalence of ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œPak OgahÃƒÂ¢Ã¢â€šÂ¬Ã‚Â in Genteng Subdistrict, Banyuwangi Regency. This type of research is empirical juridical, where the researcher describes in detail the object being studied regarding the legal effectiveness of Pak Ogah in traffic regulation from the perspective of Maqasid Al-Shariah. The research approach includes the statute approach, conceptual approach, juridical-sociological, and Maqasid Al-Shariah. Data collection was carried out using interviews and documentation, then analyzed descriptively and qualitatively. The results of the study indicate that: 1) the existence of Pak Ogah is met with both pros and cons in the reality of society; the pros are that Pak Ogah is considered to help reduce traffic congestion, while the cons are that Pak Ogah is seen as a cause of traffic jams. According to the theory of legal effectiveness and Law Number 22 of 2009 concerning Traffic and Road Transportation, Pak Ogah is an illegal profession because it lacks legal standing and is considered ineffective in assisting police duties, thus requiring regulation and training. 2) The Maqasid Al-Shariah perspective on the Pak Ogah phenomenon includes 2 out of five principles, namely Hifdz Al-Maal, where the profession of Pak Ogah becomes a job and source of livelihood for its practitioners, especially for the lower economic class, as it is favored because it does not require complicated qualifications; and Hifdz Al-Nafs, which prioritizes sustaining one's life and supporting their family, ensuring the continuity of life according to its course.